Analisis Harga Pokok Produksi dengan Metode Variabel Costing pada Produk Roti Ariska Desa Curah Kalak Jangkar Situbondo - Imamatin Listya Putri; M. Zikwan; Istianatun Najmiyah (Mazinda : Jurnal Akuntansi, Keuangan, dan Bisnis, 2023)
Determination of the cost of production (HPP) is one of the crucial foundations that can affect many aspects and have a systemic impact. Inaccuracy in identifying and calculating production costs, results in an inaccurate HPP and ultimately results in a selling price that is either too low or too high. So that the expected profit target is not achieved. In addition, the selling price becomes less competitive. Not only useful in planning, the cost of production is also useful for monitoring and controlling the company's operational costs. The research aims to produce HPP for Ariska Bread producers using the variable costing method. Data is collected through interviews, observations, and documents. Furthermore, the data were analyzed through the stages of data reduction, data presentation, and conclusions. Finally, each data is tested for its validity using the triangulation method (method) and extended observations. The conclusions of this study are: (1) the cost of producing Ariska Roti which has been running so far uses a simple method, predicting the costs to be incurred in production and adding a margin, so that the same selling price is obtained for all the flavors produced; (2) the application of the variable costing method produces a different COGS for each bread flavor variant, so that each variant actually needs to be set at a different selling price so that the company does not suffer losses.